The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.35808/ijeba/411
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Trend of Czech FDIs and their Effect to Institutional Environment

Abstract: Purpose: The goal of this paper is to explore the trend of FDIs in the Czech Republic and its changes in recent years using the gravity model. Apart from traditional variables used in FDI models we also introduce IFRS in national accounting rules. Design/Methodology/Approach: We use open-source data from the World Bank and FDI data from the Czech national bank, to analyse a panel data of bilateral FDI for 19 EU countries over the period 2008-2017 by PPML specification. Findings:We have observed significant eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…While a voluminous empirical study examines the relationship between institutional quality and economic growth, and FDI inflow and economic growth, however, the literature related to the nexus between FDI inflow and institutional quality is scanty. To the best of our knowledge, there are few studies that directly examine the relationship between FDI inflow and institutional quality (Jude and Levieuge, 2015;Buchana et al, 2012;Masron et al, 2013;Shah et al, 2016;Jindřichovská et al, 2020;Arifin, 2017;. Jude and Levieuge (2015) theoretically demonstrate that institutional quality affects FDI inflow through knowledge spillover.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a voluminous empirical study examines the relationship between institutional quality and economic growth, and FDI inflow and economic growth, however, the literature related to the nexus between FDI inflow and institutional quality is scanty. To the best of our knowledge, there are few studies that directly examine the relationship between FDI inflow and institutional quality (Jude and Levieuge, 2015;Buchana et al, 2012;Masron et al, 2013;Shah et al, 2016;Jindřichovská et al, 2020;Arifin, 2017;. Jude and Levieuge (2015) theoretically demonstrate that institutional quality affects FDI inflow through knowledge spillover.…”
Section: Introductionmentioning
confidence: 99%
“…They find no long-run and short-run causality from institutional quality to FDI inflow in the primary sector, and primary and service sectors, respectively. On the contrary, Jindřichovská et al (2020) empirically examine the impact of FDI inflow and outflow to institutional environment in the Czech Republic. Their study finds the positive impact of FDI on institutional issues.…”
Section: Introductionmentioning
confidence: 99%
“…Daude and Fratzscher (2008) affirmed the importance of strong regulatory institutions as a prerequisite for host nations to be able to attract FPI inflows. In a similar vein, the same would apply in the case of FDI inflows, as Jindřichovská et al (2020) concluded. According to them, the quality of institutions in a country is important to attract foreign capital flows.…”
Section: Discussion Of Findingsmentioning
confidence: 72%
“…Krajewski (2014) notes, that the innovative potential of EE countries is still unsatisfactory and weak, with the exception of Slovenia and Estonia. Structural features of the economies of EE countries that determine innovative potential are a large share of employment in the agricultural sector, a low share of services in GDP, major portion of the so-called problem sectors of the economy, weak financial sector, low level of technical infrastructure development (Jindrichovska et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%